2013
DOI: 10.3109/0886022x.2013.794686
|View full text |Cite
|
Sign up to set email alerts
|

Advanced IgA nephropathy with impaired renal function benefits from losartan treatment in rats

Abstract: (IgAN), independent of blood pressure changes, but the therapeutic role of ARB in advanced IgAN with impaired renal function is to be ascertained. The present study was performed to investigate the effect of losartan on advanced IgAN induced by staphylococcal enterotoxin B (SEB) combined with 5/6 nephrectomy in rats. Methods: Fifty-four male SD rats were randomly divided into three group: Rats in the model group were treated with SEB plus 5/ 6 nephrectomy, and those in the losartan group were gavaged with losa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…During week 6, the mice were intravenously administered 0.2 ml of 2 mmol/L phosphate buffer containing 0.1% BSA once daily for three consecutive days. At week 8, the mice were administered staphylococcal enterotoxin (SEB, 10503027, Thermo Fisher Scientific, Waltham, MA, United States) via tail vein injection once weekly for 3 weeks at increasing doses of 0.5 mg/kg, 0.6 mg/kg, and 0.8 mg/kg ( Jia et al, 2007 ; He et al, 2010 ; Wang, Fu et al, 2013 ), during weeks 8, 9, and 10, respectively. After SEB injection at week 8, surviving model mice were divided into four groups of six mice each.…”
Section: Methodsmentioning
confidence: 99%
“…During week 6, the mice were intravenously administered 0.2 ml of 2 mmol/L phosphate buffer containing 0.1% BSA once daily for three consecutive days. At week 8, the mice were administered staphylococcal enterotoxin (SEB, 10503027, Thermo Fisher Scientific, Waltham, MA, United States) via tail vein injection once weekly for 3 weeks at increasing doses of 0.5 mg/kg, 0.6 mg/kg, and 0.8 mg/kg ( Jia et al, 2007 ; He et al, 2010 ; Wang, Fu et al, 2013 ), during weeks 8, 9, and 10, respectively. After SEB injection at week 8, surviving model mice were divided into four groups of six mice each.…”
Section: Methodsmentioning
confidence: 99%
“…In rats treated with candesartan for 12 weeks, UAE decreased, as did TGF-β, fibronectin (FN), and RAAS components. Wang et al (2013) investigated the therapeutic role of ARB in an IgA nephropathy rat model and found that administration of losartan decreased urinary protein levels and reduced serum BUN, Scr, TGF-β1, FN, α-SMA, and FGF-1, finally delaying the progression of advanced IgA nephropathy with impaired renal function. In the IDTN and RENAAL trials, ARB treatment reduced the relative risk of reaching the primary composite end point-death, doubling of serum creatinine, or end-stage renal disease-in people with type 2 diabetes with kidney involvement by 20 and 16%, respectively (Lewis et al 2001;Brenner et al 2001).…”
Section: Angiotensin Receptor Blockers (Arbs)mentioning
confidence: 99%
“…Many drugs used in clinical practice have anti-retrofibrotic effects, such as ACEI, ARB, aldosterone inhibitors, statins, endothelin receptors, beta-blockers, acetylsalicylic acid, metformin, and MMP inhibitors (Brewster and Perazella, 2004;Kanbay et al, 2009;Manns et al, 2012;Böhm et al, 2017;Rangarajan et al, 2018;Zhang et al, 2020), Among them, ACEI and ARB are the first-line drugs for the clinical treatment of CKD (KDOQI, 2012;Chen et al, 2018). The antifibrotic effect of ACEI/ARB may also arise from the preventive effect on glomerular injury induced by aldosterone or high intra-glomerular pressure (Obata et al, 1997;Wang et al, 2013). Although these drugs have shown some improvement in fibrosis, their therapeutic targets do not focus on fibrosis.…”
Section: Introductionmentioning
confidence: 99%